The Effect of Digital Marketing and Product Quality on Repurchase Interest In The Originote Skincare - Nabilah, Nanda; Nurhapipah, Nurhapipah; Hernidatiatin, Lis Tatin (Dinasti International Journal of Digital Business Management, 2024)
Marketing on purchases of The Originote has a huge influence on repurchase interest because in the current era technology such as e-commerce is used, technological advances have had a very significant impact on various aspects of business, including marketing. Support from product quality strengthens consumers' interest in repurchasing The Originote products. This research used a sample of 120 people using the Cochran formula. The results obtained were a sample size of 96 people, and this population was taken from people who used The Originote products. The results of this research show that digital marketing and product quality have a positive and significant influence on interest in repurchasing The Originote products. This research uses validity testing, reliability testing, classical assumption testing, regression analysis, and hypothesis testing.